A Functional Form of The Zenga Curve Based on Rohde’s Version of the Lorenz Curve - Muhammad Fajar; Setiawan; Nur Iriawan; Eko Fajariyanto (Jurnal Matematika MANTIK, 2022)
The Zenga curve is a tool to measure income inequality that represents the income ratio between the bottom income group and the top income group. A proper Zenga curve is a Zenga curve that can detect variations in the Ratio. In this paper, we derive the functional form of the Zenga curve from Rohde's Lorenz curve model. The result of this paper is that the functional form of the Zenga curve from Rohde's version of the Lorenz curve model is a constant. It cannot represent the truly happening phenomenon of inequality.